Problematics of Increasing The Professionalism of Madrasah Ibtidaiyah Teachers - Dewi Ayu Oktafiani (Program Pascasarjana UIN Sumatera Utara, 2023)
This research was based on various challenges encountered by MI Rifa'iyah Kampil in increasing the professionalism of teachers in the madrasah, including the qualifications of educators who are not yet relevant, the limitations of teachers in understanding the curriculum and the low motivation of teachers who are still the background for formulating strategies. Madrasah head in increasing teacher professionalism at MI Rifa'iyah Kampil. The role of the madrasa head in improving the quality of education at MI Rifa'iyah Kampil is very influential on teacher professionalism. The aim of this research is to describe the increase in teacher professionalism at MI Rifa'iyah Kampil and to describe the problems of increasing teacher professionalism at MI Rifa'iyah Kampil. This research is field research with a qualitative approach..Penelitian ini dilatarbelakangi oleh berbagai tantangan yang ditemui oleh MI Rifa'iyah Kampil dalam meningkatkan profesionalisme guru di madrasah tersebut, di antaranya yaitu kualifikasi pendidik yang belum relevan, keterbatasan guru dalam memahami kurikulum dan masih rendahnya motivasi yang dimiliki oleh guru masih menjadi latar belakang penyusunan strategi kepala madrasah dalam meningkatkan profesionalisme guru di MI Rifa'iyah Kampil. Peran kepala madrasah dalam meningkatkan kualitas pendidikan di MI Rifa'iyah Kampil menjadi sangat berpengaruh terhadap profesionalisme guru. Tujuan dari penelitian ini adalah untuk mendeskripsikan problematika dalam peningkatan profesionalisme guru di MI Rifa'iyah Kampil. Penelitian ini merupakan penelitian lapangan (field research) dengan pendekatan kualitatif.